Pengaruh Pupuk Kandang Plus Terhadap Pertumbuhan dan Produksi Jagung Manis di Purwodadi, Kabupaten Grobogan - Silfareda Aulia; Dwi Retno Lukiwati; Eny Fuskhah (Universitas Sebelas Maret, 2021)
Manure plus is manure’s nutrition improvement by the addition of organic N from (L. leucocephala) and nature P from (rock phosphate). The aim of this research are to evaluate the effect of ‘manure plus’ on growth and production of sweet corn. The method used was Randomized Block Design with seven treatments and four replications. The treatments were P0 (ZA + TSP), P1 (Cattle manure + ZA + TSP), P2 (Goat manure + ZA + TSP), P3 (Poultry manure + ZA + TSP), P4 (Cattle manure + RP + + Leucaena leucocephala), P5 (Goat manure + RP+ Leucaena leucocephala), P6 (Poultry manure + RP + Leucaena leucocephala). KCl gave to all plots (150 kg K2O/ha). The parameters were plant height, leaf’s number, cob length, cob diameter, sum of seed row, and production of sweet corn. Data subjected to analysis of variance and followed DMRT at α = 5%. The result showed that cob diameter and sum of seed row of P4 had no significantly different compared to P1, P5 had no significantly different compared to P2, P6 had no significantly different compared to P3. The leaf’s number of P4 had no significantly different compared to P1, P5 had no significantly different compared to P2, whereas P3 had leaf’s number more than P6. All treatments had no significant effect towards plant height, cob length and production of sweet corn. Based on the research, manure plus can be used to substitute the role of manure + ZA + TSP.